THE USES OF STYLE LANGUAGE BASED ON SENTENCE STRUCTURE ON ADVERTISING (Studies in Rent Pocari Sweat Japanes Language From the 1980s until the 2000s ) - Rahima Zakiya Rujiana; Nana Rahayu; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study discusses about the use of language in the discourse style of Pocari Sweat advertisements broadcast on the electronic media, especially television associated with verbal messages spoken in terms of sentence structure. In addition, this study also describes how developments and trends in the use of language styles based on the period the ad is appearing in the 1980s to the 2000s. As the data is randomly selected 15 pieces of advertising Pocari Sweat Japanese language which can be seen on youtube streaming sites. Data were analyzed by the method of introspection to prove the validity of the data and distributional methods to analyze the data. Based on the theory of language style proposed by Gorys Keraf analysis shows bahwasannya discourse Pocari Sweat Japanese-language ad which there are stylistic climax, anti-climax, parallelism, antithesis, and repetition of the type of anaphora, epizeuksis, and epanalepsis. Where in a single discourse ads are ads that have 3 types of style, two kinds of style, and some have only one type of style.Keywords: language style,sentence structure,advertaisment